The selves of South African expatriate teachers influencing teacher leadership practices in Gulf schools - Inbanathan Naicker; Ashkelon Govender (Perspectives in Education)
The scholarship on teacher leadership has witnessed significant growth over the past two decades, yielding a plethora of research highlighting this phenomenon’s complexities. However, a notable gap persists in the extant literature, namely, the nexus between teacher identity, the multifaceted selves of educators, and teacher leadership praxis. This study seeks to address this knowledge gap by exploring how the personal and professional lived experiences of South African expatriate teachers inform their teacher leadership practices in Gulf Cooperation Council (GCC) country schools. This study used a qualitative research design to use narrative inquiry as its methodological framework. A purposive sampling strategy was employed to select six South African expatriate teachers from GCC countries. Narrative vignettes, constructed from field texts generated through narrative interviews and photo-elicitation, were used to illustrate how personal and professional identities shape teacher leadership praxis. The findings of this study reveal that particular personal identities, such as being a compassionate mother, contribute to the development of nurturing teacher leadership practices. Conversely, professional identities, such as being a self-directed teacher-learner, influence teacher leadership practices about teacher development. This research underscores the significance of acknowledging and mobilising expatriate teacher leaders’ personal and professional experiences as assets to enhance teaching and learning.